ESSENTIAL CHARACTERISTICS OF TRANSACTION EXPENSES IN EDUCATION SPHERE - L. V. Vorontsova; T. V. Kramin; M. V. Kramin (Russian Journal of Economics and Law)
The article presents the results of study of conceptual framework of transaction expenses conception, gives some classifications and typology of transaction expenses and introduces some features of transaction expenses in the educational institution. The authors used the institutional approach in the work.